Clinical and economic analysis of voriconazole using for treatment of invasive aspergillosis in Russian Federation - V. I. Ignatieva; M. V. Avksentieva (Онкогематология, 2015)
Introduction. Based on clinical studies data voriconazole is recommended as the drug of choice for treatment of invasive aspergillosis (IA) – a widespread infectious complications occurring in immunocompromised patients and is characterized by severe clinical course and high mortality. The aim of this study was to assess the cost-effectiveness of voriconazole compared to other preparations recommended in the Russian practice for the treatment of IA in adult patients. Materials and methods. The authors constructed a «decision tree» type of model, which compared the three treatment alternatives for the IA in adult patients, depending on the drug in first-line therapy: 1) voriconazole, 2), caspofungin, or 3) amphotericin B lipid complex (LC). Efficacy was assessed as the probability of patient survival within 14 weeks of starting treatment. We took into account the drugs cost and an increase in the hospitalization duration due to the development of serious adverse events. The model parameters were determined on the basis of the published results of clinical studies, the costs were calculated on the basis of medicines prices in the public procurement and the average bed-day cost in system of obligatory health insurance. Probabilistic sensitivity analysis was performed. Results. It has been shown that the use of voriconazole for treatment of IA is the dominant strategy compared to the use of caspofungin and amphotericin B LC, providing cost reduction while achieving maximum effect. Probabilistic sensitivity analysis (1000 simulations) showed stability of the revealed pattern. Conclusion. The use of voriconazole in the treatment of IA allows to save the greatest number of lives at minimal cost compared to other preparations recommended in the Russian practice.